PENGARUH LIQUIDITY, FIRM SIZE, GROWTH OPPORTUNITY, FINANCIAL DISTRESS, DAN MANAGERIAL OWNERSHIP TERHADAP KEPUTUSAN LINDUNG NILAI (HEDGING) DENGAN LEVERAGE SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2018) - Muhammad Affan; Prasetiono Prasetiono (Faculty of Economics and Business Diponegoro University, 2022)
Globalization that we do not realize brings risks to every multinational company that trades acrosscountries. The biggest risk that is often faced by companies conducting cross-border business transactions is the risk of changes in foreign exchange exposure. The impact of unexpected changes in foreign exchange exposure can provide large losses for the company. An alternative strategy to minimize foreign exchange risk can be done by hedging. This study aims to analyze the effect of liquidity, firm size, growth opportunity, financial distress, and managerial ownership on hedging decision making with leverage as a moderating variable.The population in this research are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The sample in this research amounted to 57 companies selected using the purposive sampling technique. Sample data are collected from IDX and the company’s annual report. Logistic regression analysis was used in this research model because the type of data is binary data. By logistic regression analysis, it can be seen how the independent variables affect the probability of the company to hedge.The results of this research provide empirical evidence that variable liquidity (CR), firm size (SIZE), growth opportunity (MBVE), financial distress (GScore), and Managerial Ownership (MO) have no effect on hedging decision making. The results also showed that the Leverage as a moderating variable had no effect on the relationship between liquidity on hedging decisions and also had no effect between growth opportunity on hedging decisions but influenced the relationship between financial distress on hedging decisions. From the test result of logistic regression showed that the variable of liquidity, firm size, growth opportunity, financial distress, and managerial ownership in explaining the probability of using derivative hedging was 15% and the rest is explained by other variables outside the model.Group.